Design of a Book and Thesis Recommendation System based on Ontologies associated with Thesaurus: The Case of the Libraries of the UNMSM - Huamán Acuña, Denis G. (2018)
The increase in the number of books, texts, theses and others makes traditional search systems of literature on a particular subject are complex and slow, not always obtaining good results. Even worse if it is about recommending a particular book, based on knowledge of the quality of its content. This is the very particular case of the libraries of the UNMSM, since there is no automated help for the recommendation of books and physical theses.Therefore, it is proposed to design and implement a book and thesis recommendation system for UNMSM libraries through the recommendation technique based on Ontologies associated with Thesauri. An ontological model was designed for the recommendation of books and a model of recommendation for the theses because the objective of the recommendation of both literatures is different, while the book recommendation seeks to increase the knowledge of the users, the thesis recommendation helps to select a research topic or find a bibliographic reference adjusted to the topic of user research.